2017
DOI: 10.1016/j.jaci.2016.08.050
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune chronic spontaneous urticaria: What we know and what we do not know

Abstract: Chronic spontaneous urticaria (CSU) is a mast cell-driven skin disease characterized by the recurrence of transient wheals, angioedema, or both for more than 6 weeks. Autoimmunity is thought to be one of the most frequent causes of CSU. Type I and II autoimmunity (ie, IgE to autoallergens and IgG autoantibodies to IgE or its receptor, respectively) have been implicated in the etiology and pathogenesis of CSU. We analyzed the relevant literature and assessed the existing evidence in support of a role for type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
203
0
27

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 279 publications
(235 citation statements)
references
References 95 publications
5
203
0
27
Order By: Relevance
“…Thus, the role of total IgE in CSU should be better characterized in further research. IgG-anti-IgE/FceRI autoantibodies play a role in a subpopulation of CSU patients (8). We observed that positive ASST is associated with more severe disease, higher serum levels of CRP and D-dimer.…”
Section: To the Editormentioning
confidence: 65%
“…Thus, the role of total IgE in CSU should be better characterized in further research. IgG-anti-IgE/FceRI autoantibodies play a role in a subpopulation of CSU patients (8). We observed that positive ASST is associated with more severe disease, higher serum levels of CRP and D-dimer.…”
Section: To the Editormentioning
confidence: 65%
“…Studies showing the presence of IgG‐anti‐IgE and IgG‐anti‐FcεRI antibodies are summarized in Table . The evidence in support of this mechanism of CSU has been reviewed recently . Removal of IgE and subsequent loss of mast cell FcεRI would explain the slow onset of action of omalizumab seen in up to 30% of patients responding to omalizumab .…”
Section: Purported Mechanisms Of Chronic Urticariamentioning
confidence: 99%
“…IgE antibodies to local autoallergens, or Type 2b, viz. IgG autoantibodies to IgE or its receptor, is considered to be the most frequent causes of CSU . In both cases, the mast cell is likely to be the axial cell in producing the wheals.…”
Section: Purported Mechanisms Of Chronic Urticariamentioning
confidence: 99%
“…Abdominal attacks are very painful and might mimic acute abdomen with a risk of surgery being performed [96]. In patients with associated urticaria, the angio-oedematous lesions can be the result of an autoimmune process [97, 98]. Angio-oedema can be mistaken for anaphylaxis and vice versa, since laryngeal angio-oedema is one of the most severe manifestations of anaphylaxis [99].…”
Section: Differential Diagnosesmentioning
confidence: 99%